Does Executive MBA Deliver? Exploration of Developmental Outcomes and Participants’ Perceptions of Delivery Effectiveness - Naveda Kitchlew (Journal of Management and Research, 2020)
Critics of the value of the Executive MBA program have not adequately considered the perceptions of Executive MBA students. This paper evaluates performance of an Executive MBA program by exploring students’ preferred developmental outcomes and perceptions about the effectiveness of their Executive MBA program towards delivering the targeted outcomes. Interviews, focus groups and survey were conducted with program’s directors, staff, and current and graduated students in a large privately run university in Punjab province of Pakistan. As a result of a rigorous process, the study identified twenty-seven critical outcomes under two categories namely “personal outcomes” and “professional outcomes” which students consider important and urge their Executive MBA program to deliver. On the whole students appear to be satisfied with their Executive MBA program; however, the effectiveness of their program is below their expectations. Identification of the exact outcomes in this study provide directions for Executive MBA administrators to make their curriculum and pedagogical/andragogical techniques more relevant and value-oriented for their students. Based on these findings, it is inferred that Executive MBA programs’ planning should consider students as the protagonist of their programs’ planning process.